Plant-based Natural Products as inhibitors for Efflux Pumps to Reverse Multidrug Resistance in Staphylococcus aureus: A Mini Review - Ramalingam, Shalini; Chandrasekar, Moola Joghee N.; Krishnan, Ganesh G.N.; Nanjan, Moola Joghee (Mini Reviews in Medicinal Chemistry, 2024)
Wounds provide a favourable site for microbial infection. Wound infection makes the healing more complex and does not proceed in an orchestrated manner leading to the chronic wound. Clinically infected wounds require proper antimicrobial therapy. Broad-spectrum antibiotics are usually prescribed first before going to targeted therapy. The current conventional mode of therapy mainly depends on the use of antibiotics topically or systemically. Repeated and prolonged use of antibiotics, however, leads to multidrug resistance. Staphylococcus aureus is the most common multidrugresistant microorganism found in wounds. It effectively colonizes the wound and produces many toxins, thereby reducing the host immune response and causing recurrent infection, thus making the wound more complex. The overexpression of efflux pumps is one of the major reasons for the emergence of multidrug resistance. Inhibition of efflux pumps is, therefore, a potential strategy to reverse this resistance. The effective therapy to overcome this antibiotic resistance is to use combination therapy, namely the combination of an inhibitor, and a non-antibiotic compound with an antibiotic for their dual function. Many synthetic efflux pump inhibitors to treat wound infections are still under clinical trials. In this connection, several investigations have been carried out on plant-based natural products as multidrug resistance-modifying agents as they are believed to be safe, inexpensive and suitable for chronic wound infections.
Keywords: Staphylococcus aureus